Analysis of Transparency and Accountability of the Health Operational Assistance (BOK) Budget at Sirombu Inpatient Health Center - Zai, Agus Ringanto; Zebua, Serniati; Kakisina, Sophia Molinda; Telaumbanua, Aferiaman (Golden Ratio of Data in Summary, 2024)
Health Operational Assistance (HOA) is a fund that is used to ease the public burden on financing the health sector, especially service in community health centers, reduction in maternal mortality, infant mortality and malnutrition. Puskesmas Sirombu as a health service unit is used as a medical center for the welfare of the community, but in reality the Puskesmas Sirombu has not been optimal in realizing the budgeted funds. This study aims to determine the transparency and accountability of budget execution Bantuan Operasional Kesehatan (BOK) at Puskesmas Rawat Inap Sirombu in 2021. The research sample was taken using the method purposive sampling (specific goals or criteria). The data analysis technique used is triangulation method which combines in-depth interviews and document searches and triangulation of sources using different information to do cross check information from several sources, to improve the results of the data obtained when getting different data. Based on the research results, it can be concluded that the Puskesmas Sirombu has implemented its transparency and accountability well but has not been optimal in managing the budget for transportation assistance for Health Operational Officers (BOK), this can be seen from the fact that some of the budget was not realized.